The Vile Victorians - Terry Deary (Bath, United Kingdom Scholastic Children's Book, 1994)
Single CD. Running time: 60 minutes. A book about the Victorians by Horrible Histories.
Keywords: History of Countries -- History of Countries; History of Europe -- History of Europe